Hak Asuh Anak Akibat Perceraian Dari Perkawinan Campuran Dalam Hukum Perdata Internasional Persepektif MaqaL AL-Di>N ‘At{Iyyah - Naufal Rifqi Nasution (Mediation : Journal Of Law, 2022)
Due to the influence of globalization in Indonesia, there are a lot of people who carry out mixed marriages or marriages from different countries. Researchers focus on the impact of divorce from mixed marriages, namely about the struggle for child custody or child custody h{ad{a>nah. From a historical perspective, the decision on child custody in mixed marriages focuses on Law Number 62 of 1958 concerning Citizenship. In this case, the ius sanguinis principle is used as an absolute principle, but this law has drawn a lot of controversy. The results of this study explain that child custody or h{ad{a>nah in mixed marriages is determined with the concept of prioritizing happiness for children by considering the review of Maqa<s{id Al-Usrah Jama>l Al-di>n ‘At{iyyah which has seven purposes of marriage, when viewed from Maqa<s{id Al-Usrah Jama>l Al-di>n ‘At{iyyah, the researcher gives a stigma that child custody falls into the hands of a mother.